AB0455 Impact of one-year treatment with biotechnologic drugs on work disability and activity impairment in patients with rheumatoid arthritis. (12th June 2018) - Manara, M.; Caporali, R.; Gorla, R.; Fusaro, E.; Pellerito, R.; Rocchetta, P.A.; Sarzi Puttini, P.; Capri, S.; Sinigaglia, L.
Abstract : Background: Disease activity significantly impacts on work ability of patients with Rheumatoid Arthritis (RA). Biologic agents can control disease activity, but their effects on productivity outcomes were not adequately investigated in Italian population. Objectives: Aim of the study was to evaluate the impact of biologic therapy on work productivity outcomes in a cohort of biologic-naïve patients with active RA from northern Italy. Methods: This is a multicentre prospective study on patients with active RA in working age (18–65 years), scheduled to undergo their first biologic treatment. Demographics and clinical data were collected at baseline and at 6 and 12 months, together with productivity outcomes assessed with the RA-specific work productivity survey (WPS-RA) 1 and the Health and Labour Questionnaire (HLQ) 2 . Primary outcome was the productivity loss or gain after 1 year of treatment. Results: We included 100 patients from 7 rheumatology centres in northern Italy with active RA [mean DAS28: 5, 1 (SD 0, 9), median SDAI: 25, 2 (IQR 18, 7–33, 2)]. Most of them were females (85%), with a mean age of 49, 1 (SD: 10, 3) years and a median disease duration of 7 (IQR: 3–14) years. Patients were treated with TNF-inhibitors (68%), Abatacept (24%) or Tocilizumab (8%). At baseline 39 patients were unemployed. After 1 year of treatment, 85 patients were still on follow-up, with an improvement in all indexes of disease activity [mean DAS28: 2, 8 (SD 1, 3), median SDAI: 5, 1 (IQR 1, 9–12, 9)]. A significant reduction in number of days of work missed (absenteeism) and of reduced productivity (presenteeism) was observed in employed subjects, as well as a significant decrease in number of days missed of household work and social activities in all the study population (table 1). Conclusions: One year of treatment with biological drugs was associated with a significant improvement in outcomes related to productivity both within and outside home in a cohort of patients with RA. References: [1] Osterhaus JT. Arthritis Res Ther. 2009;11:R73. [2] Van Roijen L. Int J Technol Assess Health Care1996;12:405–15. Disclosure of Interest: M. Manara: None declared, R. Caporali: None declared, R. Gorla: None declared, E. Fusaro: None declared, R. Pellerito: None declared, P. A. Rocchetta: None declared, P. Sarzi Puttini: None declared, S. Capri Consultant for: Pfizer, L. Sinigaglia: None declared